Nutrient and protein profiling of different parts of Hippocampus abdominalis: high value utilization of by-products - Fei Li; Jiayi Ren; Hongyi Li; Jing Yu; Yuhan Wang; Tiantian Zhang; Yong Xue; Gang Yu (Frontiers in Marine Science, 2026)
Introduction This study aimed to systematically compare the tissue specific nutrient and protein profiles of the head, body, and viscera of farmed Hippocampus abdominalis . Methods A total of 90 individuals were dissected into three anatomical regions: head, body (including trunk and tail), and viscera. All measurements were performed on three independent biological replicates (n = 3) . Results The results revealed that the viscera, though often discarded as a processing by product, exhibited the most balanced essential amino acid profile and the highest protein quality indices. In contrast, the body was rich in structural proteins and collagen, while the head contained high concentrations of minerals (especially magnesium and zinc) as well as proteins associated with neural and visual functions. Discussion These tissue specific functional specializations provide a molecular basis for the value added utilization of seahorse by products and offer practical insights for sustainable aquaculture practices.